Adhesive resin composition

JP7936726B2Active Publication Date: 2026-10-16KURARAY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022205720
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2026-10-16
Estimated Expiration
2042-12-22

AI Technical Summary

Benefits of technology

【0008】 本発明の接着性樹脂組成物は、耐熱性に優れるとともに、ポリビニルアルコール系樹脂層と生分解性樹脂層の両方に対する接着強度に優れている。そのため、食品等の包装材料として好適に使用できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007936726000001
    Figure 0007936726000001
  • Figure 0007936726000002
    Figure 0007936726000002
Patent Text Reader

Abstract

To provide an adhesive resin composition excellent in heat resistance and excellent in adhesive strength to both a polyvinyl alcohol resin layer and a biodegradable resin layer.SOLUTION: The adhesive resin composition of the present invention contains 3-24 pts.mass of a polyol (B) and 0-40 pts.mass of starch or modified starch (C) based on 100 pts.mass of a biodegradable polyester resin (A). The total amount of the polyol (B) and the starch or the modified starch (C) is 44 pts.mass or less. The biodegradable polyester resin (A) has an elongation at break of 50% or more as measured according to ISO 527-1. The polyol (B) has a glass transition temperature of -10°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive resin composition, a laminate including an adhesive layer comprising the adhesive resin composition, and a food packaging material and a coffee capsule including the adhesive layer or the laminate.

Background Art

[0002] Plastics are widely used as packaging materials due to their high moldability, strength, water resistance, transparency and the like. However, plastics have poor biodegradability, and if discarded into the natural environment after use, they may persist for a long period of time and cause environmental destruction. In recent years, in response to this situation, biodegradable resins that are biodegraded or hydrolyzed in soil or water and are useful for preventing environmental pollution have attracted attention, and practical application of packaging materials using biodegradable resin compositions has been advanced. As a resin composition used for packaging materials, for example, Patent Document 1 describes a resin composition containing a biodegradable polyester such as polylactic acid, a polysaccharide such as starch, and a polyhydric alcohol such as glycerin.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0004] Such biodegradable packaging materials usually have a multilayer structure, and specific examples thereof include laminates including a biodegradable resin layer, an adhesive layer, and a polyvinyl alcohol-based resin layer. However, according to studies by the present inventors, it has been found that when the adhesive layer is formed from a conventional resin composition, it is difficult to develop sufficient adhesive strength for both the biodegradable resin layer and the polyvinyl alcohol-based resin layer. Furthermore, it has been found that conventional resin compositions have poor heat resistance and may not be able to suppress coloring that can occur at high temperatures in some cases.

[0005] Therefore, the object of the present invention is to provide an adhesive resin composition that has excellent heat resistance and excellent adhesive strength to both a polyvinyl alcohol-based resin layer and a biodegradable resin layer, a laminate including an adhesive layer containing the adhesive resin composition, and a food packaging material and coffee capsules including the adhesive layer or the laminate. [Means for solving the problem]

[0006] The inventors of the present invention have conducted extensive research to achieve the above objectives and have found that the above problems can be solved if the content of biodegradable polyester (A), polyol (B), and starch or modified starch (C) in the adhesive resin composition, as well as the total amount of (B) and (C), are within a specific range, and furthermore, if the elongation at break of the biodegradable polyester (A) and the glass transition temperature of the polyol (B) are within a specific range, then the present invention can be completed. That is, the present invention encompasses the following preferred embodiments.

[0007] [1] An adhesive resin composition comprising 100 parts by mass of biodegradable polyester resin (A), 3 to 24 parts by mass of polyol (B), and 0 to 40 parts by mass of starch or modified starch (C), wherein the total amount of polyol (B) and starch or modified starch (C) is 44 parts by mass or less, the biodegradable polyester resin (A) has a break elongation of 50% or more as measured in accordance with ISO 527-1, and the glass transition temperature of polyol (B) is -10°C or higher. [2] The adhesive resin composition according to [1], wherein the melting point of the biodegradable polyester resin (A) is 70°C or higher. [3] The adhesive resin composition according to [1] or [2], wherein the biodegradable polyester resin (A) comprises an aromatic-aliphatic copolymer polyester resin. [4] The adhesive resin composition according to [3], wherein the aromatic-aliphatic copolymer polyester resin is polybutylene adipate terephthalate. [5] The adhesive resin composition according to any one of [1] to [4], wherein the polyol (B) is at least one selected from the group consisting of maltitol, sorbitol, and trehalose. [6] An adhesive resin composition according to any one of [1] to [5], which does not contain starch or modified starch (C). A laminate comprising an adhesive layer comprising an adhesive resin composition as described in any of [7][1] to [6]. [8] The laminate according to [7], comprising a biodegradable resin layer, the adhesive layer, and a polyvinyl alcohol-based resin layer in this order. A food packaging material comprising an adhesive layer comprising an adhesive resin composition according to any of [9][1] to [6], or a laminate according to [7] or [8]. A coffee capsule comprising an adhesive layer comprising an adhesive resin composition according to any one of

[10] [1] to [6], or a laminate according to [7] or [8]. [Effects of the Invention]

[0008] The adhesive resin composition of the present invention exhibits excellent heat resistance and superior adhesive strength to both the polyvinyl alcohol-based resin layer and the biodegradable resin layer. Therefore, it can be suitably used as a packaging material for food and the like. [Modes for carrying out the invention]

[0009] [Adhesive resin composition] The adhesive resin composition of the present invention contains 100 parts by mass of biodegradable polyester (A), 3 to 24 parts by mass of polyol (B), and 0 to 40 parts by mass of starch or modified starch (C), wherein the total amount of polyol (B) and starch or modified starch (C) is 44 parts by mass or less, the biodegradable polyester (A) has a breaking elongation of 50% or more as measured in accordance with ISO 527-1, and the glass transition temperature (sometimes abbreviated as Tg) of polyol (B) is -10°C or higher. In this specification, biodegradable polyester resin (A) may be referred to as "component (A)", polyol (B) may be referred to as "component (B)", starch or modified starch (C) may be referred to as "component (C)", and polyvinyl alcohol may be abbreviated as PVA. In this specification, the upper and lower limits can be arbitrarily combined.

[0010] The inventors of the present invention have investigated the interlayer adhesion and heat-induced discoloration of laminates and have found that, in an adhesive resin composition, if the content of components (A), (B), and (C) [sometimes abbreviated as components (A)~(C)], the total amount of components (B) and (C), the elongation at break of component (A), and the Tg of component (B) are within a specific range, it is possible to improve the adhesive strength to both the PVA-based resin layer and the biodegradable resin layer, as well as improve heat resistance and suppress discoloration at high temperatures. This is presumed to be because a specific amount of component (A) with an elongation at break of 50% or more improves the toughness and strength of the composition itself and enables high adhesion to the biodegradable resin layer; a specific amount of component (B) with a Tg of -10°C or higher enables high adhesion to the PVA-based resin layer while suppressing bleed-out and a decrease in toughness; and a specific amount of component (C) improves heat resistance while suppressing a decrease in toughness. In this specification, adhesive strength can be evaluated by a peel test and refers to the peel strength between the adhesive resin composition (adhesive layer) and other layers such as a PVA-based resin layer or a biodegradable resin layer. Here, the failure of the adhesive layer before peeling in the peel test is referred to as "cohesive failure," and in the case of "cohesive failure," the adhesive strength is evaluated based on the strength at the time of cohesive failure. Therefore, adhesive strength includes the adhesive force of the adhesive resin composition to other layers, as well as the strength and toughness of the composition itself. In this specification, heat resistance refers to the property of being able to suppress discoloration even at high temperatures and can be evaluated, for example, by the method described in the examples.

[0011] <Biodegradable polyester resin (A)> The adhesive resin composition of the present invention contains a biodegradable polyester resin (A) having a break elongation of 50% or more as measured in accordance with ISO 527-1. By including such a biodegradable polyester resin (A), the toughness of the adhesive resin composition itself is increased while maintaining biodegradability, and the adhesive strength to the biodegradable resin layer and the PVA resin layer can be improved. Biodegradability refers to a property that can be chemically decomposed by actions such as hydrolysis, enzymatic decomposition, or microbial decomposition, and preferably refers to a material that conforms to the biodegradability criteria specified in EN13432 or ASTM6400. That is, a material is considered biodegradable if, when placed in a composting environment, 90% of it disintegrates into particles with an average size of less than 2 mm within 12 weeks, and after 6 months, at least 60% of it decomposes into carbon dioxide and / or water according to ASTM6400, or at least 90% according to EN13432.

[0012] The biodegradable polyester resin (A) has an elongation at break of 50% or more. If the elongation at break is less than 50%, the toughness of the composition itself is insufficient, and the adhesive strength tends to decrease. The elongation at break of the biodegradable polyester resin (A) is 50% or more, preferably 100% or more, more preferably 200% or more, even more preferably 400% or more, even more preferably 600% or more, particularly preferably 800% or more, and particularly more preferably 900% or more. If the elongation at break is above the lower limit of the above, the toughness increases, and thus the adhesive strength can be improved. The upper limit of the elongation at break is usually 5000% or less, preferably 3000% or less, and more preferably 2000% or less. If the elongation at break is below the upper limit of the above, the decrease in the elastic modulus and maximum strength of the adhesive composition can be suppressed, and thus the decrease in adhesive strength can be suppressed. The elongation at break can be measured in accordance with ISO 527-1, and can be measured, for example, by the method described in the examples. When using two or more biodegradable polyester resins (A) in combination, the elongation at break is determined by measuring the elongation at break of the mixture of biodegradable polyester resins used, and the resulting elongation at break is taken as the elongation at break of biodegradable polyester resin (A).

[0013] The biodegradable polyester resin is not particularly limited as long as it has a break elongation of 50% or more and the above-mentioned biodegradability, and may be a petroleum-derived biodegradable resin or a biodegradable resin derived from living organisms. Examples of biodegradable polyester resins include aliphatic polyester resins, aromatic-aliphatic copolymer polyester resins, and aromatic polyester resins. The biodegradable polyester resin preferably contains at least one selected from the group consisting of aliphatic polyester resins and aromatic-aliphatic copolymer polyester resins, and it is more preferable to include aromatic-aliphatic copolymer polyester resins from the viewpoint of easily improving adhesive strength and heat resistance while having high biodegradability.

[0014] Examples of aliphatic polyester resins include polyalkylene monocarboxylate and polyalkylene dicarboxylate.

[0015] Examples of polyalkylene monocarboxylates include ring-opening polymers of lactones (cyclic esters). Specific examples include polycaprolactone (abbreviated as PCL).

[0016] Polyalkylene carboxylates are polycondensates of aliphatic diols (or their derivatives) and aliphatic dicarboxylic acids (or their derivatives). Examples include polybutylene succinate (abbreviated as PBS), polyethylene succinate (abbreviated as PES), and poly(butylene succinate-co-butylene adipate).

[0017] The aromatic-aliphatic copolyester resin is a polyester resin having both an aromatic moiety and an aliphatic moiety, and is a condensate of an aliphatic or aromatic diol (or a derivative thereof) and an aromatic or aliphatic dicarboxylic acid (or a derivative thereof). Examples thereof include polybutylene adipate terephthalate (abbreviated as PBAT), polybutylene succinate terephthalate (PBST), polyethylene adipate terephthalate (PEAT) and the like, and PBAT is preferred from the viewpoint of easily enhancing adhesive strength and heat resistance while having high biodegradability. These biodegradable polyester resins may be used alone or in combination of two or more kinds.

[0018] The biodegradable polyester resin (A) may be produced by a conventional method, or a commercially available product may be used. Examples of commercially available products of the biodegradable polyester resin (A) include polycaprolactone (PCL) sold under the trade name Tone (trademark) (for example, Tone P-300, P-700, P-767 and P-787, having a weight average molecular weight of about 10,000, 40,000, 43,000 and 80,000, respectively) by Union Carbide, or polycaprolactone (PCL) sold under the trade names CAPA 6800 and CAPA FB100 (having a molecular weight of 80,000 Daltons and 100,000 Daltons, respectively) by Perstorf; polyethylene succinate (PES) and polybutylene succinate (PBS) (for example, Bionolle (trademark) 1001 (PBS) and Bionolle (trademark) 6000 (PES)) sold under the trade name Bionolle (trademark) by Showa Highpolymer Co., Ltd.; polybutylene adipate (PBA) sold under the trade name Skygreen (trademark) SG100 by SK Chemicals (Korea); polybutylene adipate terephthalate (PBAT) aliphatic / aromatic copolyesters, such as Ecoflex (trademark) by BASF (Germany), or EnPOL (trademark) G8060 and EnPOL (trademark) 8000 by Ire Chemical Ltd (Seoul); and the like.

[0019] The biodegradable polyester resin (A) may be a modified biodegradable polyester resin or an unmodified biodegradable polyester resin. The modified biodegradable polyester resin is not particularly limited, and for example, it may be a modified biodegradable polyester resin obtained by graft-modifying a biodegradable polyester resin with an unsaturated carboxylic acid and / or a derivative thereof. The unsaturated carboxylic acid as the modifier is not particularly limited, and examples thereof include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, and the like. The derivative of the unsaturated carboxylic acid is not particularly limited, and examples thereof include acid anhydrides, esters, amides, imides, metal salts, and the like.

[0020] Specific examples of the derivatives of unsaturated carboxylic acids include maleic anhydride, hymic anhydride, itaconic anhydride, citraconic anhydride, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl acrylate, maleic acid monoethyl ester, maleic acid diethyl ester, itaconic acid monomethyl ester, itaconic acid diethyl ester, acrylamide, methacrylamide, maleic acid monoamide, maleic acid diamide, maleic acid-N-monoethylamide, maleic acid-N,N-diethylamide, maleic acid-N,N-monobutylamide, maleic acid-N,N-dibutylamide, fumaric acid monoamide, fumaric acid diamide, fumaric acid-N-monobutylamide, fumaric acid-N,N-dibutylamide, maleimide, N-butylmaleimide, N-phenylmaleimide, sodium acrylate, sodium methacrylate, potassium acrylate, potassium methacrylate, and the like. These unsaturated carboxylic acids and / or derivatives thereof may be used alone, or two or more thereof may be used in any optional combination and ratio. Among these, maleic acid or an anhydride thereof is particularly preferred due to its low electron density and high reactivity.

[0021] The content of the modifying agent is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, even more preferably 0.03% by mass or more, preferably 3.0% by mass or less, more preferably 1.0% by mass or less, and even more preferably 0.2% by mass or less, relative to the mass of the modified biodegradable polyester resin.

[0022] The adhesive resin composition of the present invention is an alloy containing specific amounts of components (A) to (C), and therefore can exhibit excellent adhesive strength and heat resistance to the PVA resin layer and the biodegradable resin layer without modifying the biodegradable polyester resin (A). For this reason, in a preferred embodiment of the present invention, the biodegradable polyester resin (A) is preferably an unmodified biodegradable polyester resin. When it is unmodified, a decrease in biodegradability due to modification can be prevented, and the complexity of manufacturing due to modification can also be avoided.

[0023] In a preferred embodiment of the present invention, the melting point of the biodegradable polyester resin (A) is preferably 70°C or higher, more preferably 80°C or higher, even more preferably 90°C or higher, even more preferably 100°C or higher, and particularly preferably 105°C or higher. When the melting point of the biodegradable polyester resin (A) is above the lower limit of the above, the thermoformability is more easily improved, making it easier to suppress or prevent the occurrence of wrinkles in the resulting laminate, and resulting in a better appearance. The upper limit of the melting point is preferably 300°C or lower, more preferably 200°C or lower, even more preferably 150°C or lower, even more preferably 140°C or lower, and particularly preferably 130°C or lower. When the melting point is below the upper limit of the above, the thermoformability is more easily improved, making it easier to mold the resulting laminate into a predetermined shape. The melting point can be measured by differential scanning calorimeter (DSC), for example, by the method described in the examples.

[0024] In one embodiment of the present invention, the melt mass flow rate (MFR) of the biodegradable polyester resin (A) is preferably 1.0 g / 10 min or more, more preferably 3.0 g / 10 min or more, even more preferably 5.0 g / 10 min or more, even more preferably 10 g / 10 min or more, preferably 30 g / 10 min or less, more preferably 25 g / 10 min or less, and even more preferably 20 g / 10 min or less. Having the MFR of the biodegradable polyester resin (A) within the above range makes it easier to improve adhesive strength, heat resistance, and thermoformability. The MFR can be measured in accordance with ISO 1133 under conditions of 200°C and 2.16 kg.

[0025] In one embodiment of the present invention, the weight-average molecular weight (Mw) of the biodegradable polyester resin (A) is preferably 10,000 or more, more preferably 30,000 or more, even more preferably 50,000 or more, preferably 500,000 or less, more preferably 200,000 or less, and even more preferably 100,000 or less. Having the Mw of the biodegradable polyester resin (A) within the above range makes it easier to improve adhesive strength, thermoformability, and heat resistance.

[0026] In one embodiment of the present invention, the number average molecular weight (Mn) of the biodegradable polyester resin (A) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 20,000 or more, preferably 200,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less. Having the above range for the Mn of the biodegradable polyester resin (A) makes it easier to improve adhesive strength, thermoformability, and heat resistance. Furthermore, the Mw and Mn of the biodegradable polyester resin (A) can be determined by gel permeation chromatography (GPC) and converted to standard polystyrene equivalents, for example, by the method described in the examples.

[0027] In one embodiment of the present invention, the content of the biodegradable polyester resin (A) is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and even more preferably 65% ​​by mass or more, based on the mass of the adhesive resin composition, and may be, for example, 75% by mass or more or 85% by mass or more. When the content of the biodegradable polyester resin (A) is above the lower limit of the above, the adhesion to the biodegradable resin layer tends to increase due to improved affinity to the biodegradable resin layer. In addition, the adhesive strength to the biodegradable resin layer and the PVA resin layer tends to increase due to improved toughness and strength of the composition itself. The content of the biodegradable polyester resin (A) is preferably 96.5% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less, based on the mass of the adhesive resin composition. When the content of the biodegradable polyester resin (A) is below the upper limit of the above, the adhesion to the PVA resin layer tends to increase.

[0028] [Polyol (B)] The adhesive resin composition of the present invention contains a polyol (B). The glass transition temperature (Tg) of the polyol (B) contained in the adhesive resin composition is -10°C or higher, and its content is 3 to 24 parts by mass, thereby improving adhesive strength and heat resistance. The polyol may be of artificial or natural origin, preferably of natural origin, and more preferably a sugar alcohol.

[0029] In the adhesive resin composition of the present invention, the Tg of polyol (B) is -10°C or higher. If the Tg of polyol (B) is below -10°C, the adhesive strength tends to decrease due to bleed-out of polyol (B), etc. The Tg of polyol (B) is -10°C or higher, preferably -5°C or higher, more preferably 0°C or higher, even more preferably 5°C or higher, even more preferably 15°C or higher, and particularly preferably 25°C or higher. If the Tg of polyol (B) is above the lower limit of the above, bleed-out, etc. can be suppressed and the adhesive strength can be increased. The Tg of polyol (B) is preferably 150°C or lower, more preferably 130°C or lower, even more preferably 100°C or lower, even more preferably 80°C or lower, and particularly preferably 60°C or lower. Adhesive strength can also be easily improved when the Tg of polyol (B) is below the upper limit of the above. The Tg of polyol (B) can be measured by differential scanning calorimeter (DSC), and can be measured, for example, by the method described in the examples. When using two or more polyols in combination, the Tg is determined by measuring the Tg of the polyol mixture used and using the resulting Tg as the Tg of polyol (B).

[0030] Examples of polyols (B) with a Tg of -10°C or higher include maltitol, sorbitol, trehalose, lactitol, and galactitol. From the viewpoint of easily improving adhesive strength and heat resistance, polyol (B) is preferably at least one selected from the group consisting of maltitol, sorbitol, and trehalose, and preferably at least one selected from the group consisting of maltitol and sorbitol, and more preferably maltitol. These polyols may also be polyol derivatives to which alkylene oxides such as ethylene oxide and propylene oxide are added, as long as the Tg is -10°C or higher.

[0031] The polyol (B) content is 3 to 24 parts by mass based on 100 parts by mass of biodegradable polyester resin (A). If the polyol (B) content is less than 3 parts by mass and more than 24 parts by mass, the adhesive strength tends to decrease. The polyol (B) content is 3 parts by mass or more, preferably 4 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more, and may be 8 parts by mass or more or 9 parts by mass or more, based on 100 parts by mass of biodegradable polyester (A). If the polyol (B) content is above the lower limit of the above, the adhesive strength to the PVA resin layer can be increased. The polyol (B) content is 24 parts by mass or less, preferably 22 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 18 parts by mass or less, and may be 16 parts by mass or less, 14 parts by mass or less, or 12 parts by mass or less, based on 100 parts by mass of biodegradable polyester (A). When the polyol (B) content is below the above upper limit, the toughness and strength of the adhesive resin composition itself tend to increase, and the adhesive strength can be improved.

[0032] [Starch or modified starch (C)] The adhesive resin composition of the present invention may contain starch or modified starch (C). That is, the adhesive resin composition of the present invention may or may not contain starch or modified starch (C).

[0033] Examples of starches include those derived from cassava, corn, potatoes, sweet potatoes, sago, tapioca, sorghum, beans, bracken, lotus, water chestnut, wheat, rice, oats, arrowroot, peas, etc. Among these, starches derived from corn and cassava are preferred, and starches derived from corn are even more preferred. Starches can be used alone or in combination of two or more types.

[0034] The modified starch is preferably at least one selected from the group consisting of, for example, etherified starch, esterified starch, cationized starch, crosslinked starch, and amidated starch.

[0035] Examples of etherified starches include alkyl etherified starches such as methyl etherified starch; carboxyalkyl etherified starches such as carboxymethyl etherified starch; and hydroxyalkyl etherified starches such as etherified starch having a hydroxyalkyl group with 2 to 6 carbon atoms. Other examples of etherified starches include cetyl bromide, lauryl bromide, epoxidized soybean fatty alcohol, epoxidized linseed fatty alcohol; etherified starches having structural units derived from glycidyl ethers such as allyl glycidyl ether, propyl glycidyl ether, butyl glycidyl ether, decane glycidyl ether, laurylphenyl glycidyl ether, myristoyl glycidyl ether, cetyl glycidyl ether, palmityl glycidyl ether, stearyl glycidyl ether, and linolyl glycidyl ether (starch to which the glycidyl ether is bonded by etherification); and allyl etherified starch. The hydroxyalkyl etherified starch is preferably hydroxyethyl etherified starch, hydroxypropyl etherified starch, or hydroxybutyl etherified starch, and may be obtained by the reaction of starch with an alkylene oxide such as ethylene oxide, propylene oxide, or butylene oxide. The average number of hydroxyl groups used for modification is preferably 0.05 to 2 per glucose unit in the starch. The etherified starch having structural units derived from glycidyl ether is preferably etherified starch having structural units derived from glycidyl ether with 2 to 24 carbon atoms, and more preferably etherified starch having structural units derived from glycidyl ether with 6 to 24 carbon atoms.

[0036] Examples of esterified starches include esterified starches having structural units derived from carboxylic acids, such as esterified starches having structural units derived from acetic acid; esterified starches having structural units derived from dicarboxylic acid anhydrides, such as maleic anhydride, phthalic anhydride, succinic anhydride; esterified starches having structural units derived from alkanic acid carboxylic acid anhydrides, such as octanoic acid acetic anhydride, decanoic acid acetic anhydride, lauric acid acetic anhydride, myristateic acid acetic anhydride; octenyl succinic acid anhydride, nonyl succinic acid anhydride Examples include aqueous esterified starches having structural units derived from alkyl or alkenyl dicarboxylic acid anhydrides such as decyl succinic anhydride, dodecenyl succinic anhydride, octenyl maleic anhydride, nonyl maleic anhydride, decyl maleic anhydride, and dodecenyl maleic anhydride; esterified starches having structural units derived from oxoacids such as nitrate esterified starch, phosphate esterified starch, and urea phosphate esterified starch; xanthogenic acid esterified starch; and acetoacetate esterified starch. The number of carbon atoms in the carboxylic acid, the dicarboxylic acid anhydride, and the alkyl or alkenyl dicarboxylic acid may be, for example, 2 to 24, and may be 2 to 6 or 7 to 24. Furthermore, octenyl succinic anhydride or octenyl maleic anhydride are preferred as the alkyl or alkenyl dicarboxylic acid anhydride.

[0037] Examples of cationized starches include reaction products of starch and 2-diethylaminoethyl chloride, and reaction products of starch and 2,3-epoxypropyltrimethylammonium chloride.

[0038] Examples of cross-linked starches include formaldehyde cross-linked starch, epichlorohydrin cross-linked starch, phosphate cross-linked starch, and acrolein cross-linked starch.

[0039] Examples of amidated starches include starches to which aliphatic amines such as n-dodecylamine, n-hexadecylamine, n-octadecylamine, cocoamine, taloamine, hydrogenated N-talo-1,3-diaminopropane, N-hydrogenated talo-1,3-diaminopropane, and N-oleyl-1,3-diaminopropane are attached by amidation.

[0040] The starch or modified starch (C) may preferably have a water content of 5 to 15% by mass.

[0041] As for the starch or modified starch (C), from the viewpoint of easily improving adhesive strength and heat resistance, the above-mentioned modified starch is preferred, and it is preferable that it is at least one selected from the group consisting of hydroxyalkyl etherified starch (preferably etherified starch having a hydroxyalkyl group with 2 to 6 carbon atoms), etherified starch having structural units derived from glycidyl ether (preferably etherified starch having structural units derived from glycidyl ether with 6 to 24 carbon atoms), esterified starch having structural units derived from dicarboxylic acid anhydride (preferably esterified starch having structural units derived from dicarboxylic acid anhydride with 2 to 6 carbon atoms), and esterified starch having structural units derived from alkyl or alkenyl dicarboxylic acid anhydride (preferably esterified starch having structural units derived from alkyl or alkenyl dicarboxylic acid anhydride with 6 to 24 carbon atoms). These modified starches can be used alone or in combination of two or more. In this specification, the number of carbon atoms mentioned before "starch" represents the number of carbon atoms of the group substituted for one hydroxyl group in the starch (a group formed by modifying one hydroxyl group in the starch). For example, etherified starch having a hydroxyalkyl group with 2 to 5 carbon atoms indicates that the hydroxyalkyl group formed by modifying one hydroxyl group in the starch has 2 to 5 carbon atoms.

[0042] In one embodiment of the present invention, the starch or modified starch (C) may have an average amylose content of preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 0.8% by mass or more, preferably 90% by mass or less, more preferably 70% by mass or less, even more preferably 50% by mass or less, even more preferably 40% by mass or less, and particularly preferably 30% by mass or less. When the average amylose content is within the above range, the thermoformability and adhesion of the starch or modified starch (C) and the adhesive resin composition itself are easily enhanced. The amylose content can be measured, for example, by the iodine colorimetric method described in "Starch 50 No.4 158-163 (1998)". Note that the average amylose content refers to the amylose content of the one type of starch or modified starch if only one type of starch or modified starch is used, and is the weighted average of the amylose content of the two or more types of starch or modified starch if two or more types of starch or modified starch are used. Furthermore, commercially available starch or modified starch (C) may be used.

[0043] In one embodiment of the present invention, the weight-average molecular weight (Mw) of starch or modified starch (C) is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 20,000 or more, preferably 800,000 or less, more preferably 600,000 or less, even more preferably 400,000 or less, and even more preferably 200,000 or less. When the Mw of starch or modified starch (C) is within the above range, the thermoformability and adhesion of the starch or modified starch (C) and the adhesive resin composition itself are easily enhanced. The Mw of starch or modified starch (C) can be measured, for example, using GPC (gel permeation chromatography).

[0044] The starch or modified starch (C) content is 0 to 40 parts by mass based on 100 parts by mass of biodegradable polyester resin (A). If the starch or modified starch (C) content exceeds 40 parts by mass, the adhesive strength and heat resistance tend to decrease. In one embodiment of the present invention, the starch or modified starch (C) content is 40 parts by mass or less, preferably 35 parts by mass or less, more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, particularly preferably 5 parts by mass or less, particularly more preferably 3 parts by mass or less, and particularly even more preferably 1 part by mass or less. When the starch or modified starch (C) content is below the above upper limit, it is easier to suppress the decrease in the toughness of the composition itself, and high adhesive strength can be achieved while suppressing the decrease in heat resistance. Furthermore, in a preferred embodiment of the present invention, the adhesive resin composition of the present invention does not contain starch or modified starch (C). When starch or modified starch (C) is not included, excellent adhesive strength and heat resistance are easily achieved. In another embodiment of the present invention, the content of starch or modified starch (C) is preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 35% by mass or less. A starch or modified starch (C) content within the above range is advantageous from the viewpoint of biodegradability, adhesive strength, and heat resistance.

[0045] In the adhesive resin composition of the present invention, the total amount of polyol (B) and starch or modified starch (C) is 44 parts by mass or less based on 100 parts by mass of biodegradable polyester (A). If the total amount exceeds 44 parts by mass, the adhesive strength and heat resistance tend to decrease. The total amount of polyol (B) and starch or modified starch (C) is 44 parts by mass or less, preferably 43 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 35 parts by mass or less, even more preferably 30 parts by mass or less, particularly preferably 25 parts by mass or less, particularly more preferably 20 parts by mass or less, and particularly even more preferably 15 parts by mass or less. When the total amount of polyol (B) and starch or modified starch (C) is below the above upper limit, it is easier to suppress the decrease in the toughness of the composition itself, high adhesive strength can be achieved, and the decrease in heat resistance can be suppressed. The total amount of polyol (B) and starch or modified starch (C) is preferably 3 parts by mass or more, more preferably 4 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of biodegradable polyester (A). When the total amount is above the lower limit mentioned above, it is easier to increase the adhesive strength.

[0046] <Adhesive resin composition> The adhesive resin composition of the present invention contains 100 parts by mass of biodegradable polyester resin (A), 3 to 24 parts by mass of polyol (B), and 0 to 40 parts by mass of starch or modified starch (C), with the total amount of components (B) and (C) being 44 parts by mass or less. The elongation at break of the biodegradable polyester (A) is 50% or more, and the Tg of the polyol (B) is -10°C or higher. Therefore, it has excellent heat resistance, can suppress or prevent discoloration even at high temperatures (for example, when exposed to high temperatures during manufacturing or molding), and exhibits excellent adhesive strength to both the polyvinyl alcohol resin layer and the biodegradable resin layer. Accordingly, the adhesive resin composition of the present invention can be suitably used as a packaging material for food and the like. Furthermore, in one embodiment of the present invention, the adhesive resin composition of the present invention also has excellent thermoformability, and the resulting laminate can be easily molded into a predetermined shape.

[0047] In one embodiment of the present invention, the total amount of components (A) to (C) contained in the adhesive resin composition of the present invention may be preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and particularly more preferably 95% by mass or more, based on the mass of the adhesive resin composition, from the viewpoint of easily increasing adhesive strength and heat resistance, for example, it may be 97% by mass or more or 99% by mass or more. Furthermore, the adhesive resin composition of the present invention may consist of a biodegradable polyester (A), a polyol (B), and starch or modified starch (C).

[0048] In one embodiment of the present invention, the adhesive strength of the adhesive resin composition of the present invention to the PVA resin layer is preferably 5 N / 25 mm or more, more preferably 10 N / 25 mm or more, even more preferably 15 N / 25 mm or more, even more preferably 20 N / 25 mm or more, particularly preferably 30 N / 25 mm or more, particularly more preferably 40 N / 25 mm or more, and particularly still more preferably 50 N / 25 mm or more. When the adhesive strength is above the lower limit of the above, it is easy to improve the strength of the resulting laminate. The adhesive strength to the PVA resin layer is usually 200 N / 25 mm or less. The adhesive strength to the PVA resin indicates the peel strength between the adhesive layer and the PVA resin layer in a multilayer sheet containing an adhesive layer made of the adhesive resin composition and a PVA resin layer. The peel strength can be measured in accordance with JIS K 6854-2 using a peel tester under conditions of a peel angle of 180°, a tensile speed of 100 mm / min, and an ambient temperature of 23°C. The adhesive strength to the PVA resin can be determined, for example, by the method described in the examples.

[0049] In one embodiment of the present invention, the adhesive strength of the adhesive resin composition of the present invention to the biodegradable resin layer is preferably 5 N / 25 mm or more, more preferably 15 N / 25 mm or more, even more preferably 25 N / 25 mm or more, even more preferably 30 N / 25 mm or more, particularly preferably 40 N / 25 mm or more, particularly more preferably 50 N / 25 mm or more, and particularly even more preferably 60 N / 25 mm or more. When the adhesive strength is above the lower limit of the above, it is easier to improve the strength of the resulting laminate. The adhesive strength to the biodegradable resin layer is usually 200 N / 25 mm or less. The adhesive strength to the biodegradable resin layer indicates the peel strength between the adhesive layer and the biodegradable resin layer in a multilayer sheet containing an adhesive layer made of the adhesive resin composition and a biodegradable resin layer. The peel strength can be measured in accordance with JIS K 6854-2 using a peel tester under conditions of a peel angle of 180°, a tensile speed of 100 mm / min, and an ambient temperature of 23°C. The adhesive strength to the biodegradable resin layer can be determined, for example, by the method described in the examples.

[0050] The adhesive resin composition of the present invention may contain biodegradable polyesters other than component (A) with an elongation at break of less than 50%, provided that the elongation at break of the biodegradable polyester resin (A) in the adhesive resin composition does not fall below 50%.

[0051] Examples of biodegradable polyesters with an elongation at break of less than 50% include PHA. PHA is a polymer with hydroxyalkanoic acid as the monomer unit. More specifically, examples include polyglycolic acid, polylactic acid (sometimes abbreviated as PLA), poly(3-hydroxyalkanoate) (abbreviated as P3HA), and poly(4-hydroxyalkanoate).

[0052] P3HA is a polymer mainly composed of 3-hydroxyalkanoic acid as its monomer unit. Examples of 3-hydroxyalkanoic acid include 3-hydroxybutyrate, 3-hydroxypropionate, 3-hydroxyvalerate, 3-hydroxyhexanoate, 3-hydroxyheptanoate, and 3-hydroxyoctanoate. P3HA may be a homopolymer or a copolymer containing two or more monomer units. Furthermore, if P3HA is a copolymer, it may be a copolymer of two or more 3-hydroxyalkanoic acid, or a copolymer of one or more 3-hydroxyalkanoic acid with a 4-hydroxyalkanoic acid such as 4-hydroxybutyrate.

[0053] Specific examples of P3HA include poly(3-hydroxybutyrate) homopolymer (abbreviated as PHB), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (abbreviated as PHBH), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (abbreviated as PHBV), and poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (abbreviated as 3HB4HB).

[0054] The biodegradable polyester with an elongation at break of less than 50% is not particularly limited as long as it is added in a range that does not cause the elongation at break of the biodegradable polyester resin (A) in the adhesive resin composition to fall below 50%, but the amount is, for example, 20% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and preferably 0% by mass or more, for example 0.1% by mass or 1% by mass or more, relative to the mass of the adhesive resin composition.

[0055] The adhesive resin composition of the present invention may contain polyols other than component (B) whose Tg is less than -10°C or whose Tg is not observed, as long as the Tg of polyol (B) in the adhesive resin composition does not fall below -10°C.

[0056] Examples of polyols with a Tg of less than -10°C or in which no Tg is observed include glycerol, xylitol, mannitol, erythritol, pentaerythritol, and dipentaerythritol.

[0057] Polyols with a Tg of less than -10°C or no observed Tg are not particularly limited, as long as they are added in a range where the Tg of polyol (B) in the adhesive resin composition does not fall below -10°C. However, the amount is, for example, 20% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and preferably 0% by mass or more, for example 0.1% by mass or 1% by mass or more, relative to the mass of the adhesive resin composition.

[0058] The adhesive resin composition of the present invention may contain additives other than components (A), (B), and (C), to the extent that they do not impair the purpose or effects of the present invention. Examples of additives include fillers, processing stabilizers, weather stabilizers, colorants, ultraviolet absorbers, heat stabilizers, light stabilizers, antioxidants, antistatic agents, flame retardants, plasticizers, lubricants, fragrances, foaming agents, deodorants, bulking agents, release agents, mold release agents, reinforcing agents, antifungal agents, preservatives, crystallization rate retarders, and other resins other than biodegradable polyester resins. These additives can be used individually or in combination of two or more.

[0059] Fillers may be added, preferably from the viewpoint of easily increasing hardness and rigidity and easily preventing blocking. Examples of fillers include inorganic fillers such as mica, kaolin, kaolinite, clay, talc, acid clay, silica, alumina, diatomaceous earth, bentonite, montmorillonite, kibushi clay, kaolinite clay, pyrophyllite, alumite, pottery clay, feldspar, asbestos, perlite, calcium carbonate, magnesium hydroxide, carbon black, vermiculite, titanium dioxide, mica, zirconium oxide, boron nitride, aluminum nitride, shirasu, glass, and glass fiber, as well as organic fillers such as urea-formaldehyde resins and melamine-formaldehyde resins. Fillers can be used alone or in combination of two or more types.

[0060] Other resins include, for example, polyphenylene ether resins, polycarbonate resins, polyamide resins such as nylon 66 and nylon 11, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, styrene resins such as polystyrene, and (meth)acrylate resins such as polymethyl methacrylate resins. These other resins can be used individually or in combination of two or more.

[0061] The amount of additives is not particularly limited as long as it is added within a range that does not impair the purpose or effect of the present invention, but is, for example, 20% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and preferably 0% by mass or more, for example 0.1% by mass or 1% by mass or more, relative to the mass of the adhesive resin composition.

[0062] The form of the adhesive resin composition of the present invention is not particularly limited and may be pellets, sheets, or films. That is, it may be pellets, sheets, or films containing or comprising the adhesive resin composition. The thickness of the sheet or film can be appropriately selected depending on the application, preferably 5 to 1000 μm, more preferably 10 to 500 μm. The thickness of the film or sheet can be measured with a thickness gauge, for example, by the method described in the examples. Furthermore, the adhesive resin composition of the present invention may contain a solvent and may be in the form of a solution or dispersion, and as the solvent, any known solvent in which the components of the composition can be dissolved or dispersed can be used.

[0063] The method for producing the adhesive resin composition of the present invention is not particularly limited, but may include, for example, a method of mixing a biodegradable polyester resin (A), a polyol (B), and optionally starch or modified starch (C) and additives. A conventional mixer, preferably a melt kneader, can be suitably used for mixing. The temperature during mixing or kneading is preferably 40°C or higher, more preferably 80°C or higher, even more preferably 100°C or higher, preferably 300°C or lower, and more preferably 200°C or lower. The rotation speed of the kneader is preferably 20 rpm or higher, more preferably 40 rpm or higher, usually 1000 ppm or lower, and preferably 500 rpm or lower. Alternatively, these components may be pre-mixed using a mixer or the like before being introduced into the melt kneader.

[0064] In one embodiment of the present invention, an adhesive resin composition can be obtained by melt-kneading using an extruder. Preferably, a twin-screw extruder can be used as the extruder. The twin-screw extruder may rotate in both directions. The rotational speed of the screws can be selected from the same range as the rotational speed of the kneader described above. The cylinder temperature can be selected from the temperature range used during mixing or kneading described above. Each component can be directly introduced into the extruder.

[0065] The molten mixture, which has been pushed through the extruder while being melted and kneaded, is extruded from the die. The die temperature is preferably 100 to 200°C, more preferably 100 to 150°C. The discharge rate is preferably 1 to 10 kg / h, more preferably 2 to 5 kg / h.

[0066] The extruded mixture (molten material) can be extruded into a sheet, film, or strand form. During this process, the mixture (molten material) is cooled and dried.

[0067] When extruding a mixture into strands, the strands can be formed into pellets by extruding them through a multi-hole strand nozzle and cutting them with a rotary cutter. To prevent the pellets from sticking together, vibration can be applied periodically or continuously, and moisture can be removed from the pellets using hot air, dehumidified air, or an infrared heater.

[0068] When the mixture is extruded into a sheet or film, the mixture can be extruded from a film-forming die and then cooled and dried while being wound up on a take-up roller. It is preferable to cool the mixture between the die and the roller to prevent it from adhering to the roller. Alternatively, a solution or dispersion of the adhesive resin composition of the present invention may be formed into a sheet or film by conventional film-forming methods (e.g., casting).

[0069] Adhesive resin compositions (for example, pelletized adhesive resin compositions) may be formed into sheets or films by conventional methods such as extrusion molding, compression molding, or press molding.

[0070] [Laminated structure] The present invention encompasses a laminate comprising an adhesive layer comprising the adhesive resin composition of the present invention. The laminate of the present invention may contain one or more adhesive layers of the present invention, and if it contains two or more layers, the composition of each adhesive layer may be the same or different. The form of the adhesive layer is not particularly limited and may be, for example, a film or a sheet. The laminate may contain other layers besides the adhesive layer of the present invention. Examples of other layers include a resin layer, paper, and other adhesive layers. The resin layer may have a different composition from the adhesive layer.

[0071] The resins constituting the resin layer are not particularly limited, and examples include polyester resins such as polyethylene terephthalate (PET); polyolefin resins such as polypropylene (PP) [preferably biaxially oriented polypropylene (BOPP)], polyethylene (PE) [preferably low-density polyethylene (LDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE)]; ethylene-vinyl acetate copolymer; polyvinyl alcohol resins such as polyvinyl alcohol and ethylene-α-olefin copolymer; biodegradable resins such as biodegradable polyester resins; and resins modified with a modifying agent such as maleic anhydride. The resin layer can be used alone or in combination of two or more types. Since the adhesive layer in the laminate of the present invention comprises the above-mentioned adhesive resin composition, it can exhibit excellent adhesive strength to both the biodegradable resin layer and the polyvinyl alcohol-based resin layer. Therefore, the laminate of the present invention preferably includes a biodegradable resin layer and / or a polyvinyl alcohol-based resin layer as resin layers, and more preferably includes both a biodegradable resin layer and a polyvinyl alcohol-based resin layer. Furthermore, by including the adhesive layer, the laminate of the present invention can improve heat resistance, biodegradability, and gas barrier properties.

[0072] The biodegradable resin layer is not particularly limited as long as it contains a biodegradable resin as its main component. Examples include the biodegradable polyester resin described in the section <Biodegradable Polyester Resin (A)> above, as well as casein, modified starch, cellulose acetate, PLA, PHB, PHBV, 3HB4HB, and PHBH. Among these, from the viewpoint of easily improving adhesive strength with the adhesive layer and biodegradability, the biodegradable resin is preferably at least one selected from the group consisting of the biodegradable polyester resin (A), PLA, PHB, PHBV, 3HB4HB, and PHBH, and more preferably at least one selected from the group consisting of PLA, PHB, PHBV, 3HB4HB, PHBH, PBAT, PBS, and PCL.

[0073] The PVA-based resin layer is not particularly limited as long as it contains a PVA-based resin as its main component. The PVA-based resin is a resin containing a vinyl ester polymer or copolymer (collectively referred to as a vinyl alcohol-based polymer). The vinyl alcohol-based polymer is a polymer that contains vinyl alcohol units as monomer units. The vinyl alcohol-based polymer is obtained by saponifying a vinyl ester-based polymer, which is obtained by polymerizing vinyl ester monomers, which are its raw material monomers. The vinyl alcohol-based polymer after saponification may contain vinyl ester units in addition to vinyl alcohol units. The vinyl alcohol-based polymer may also be a modified vinyl alcohol-based copolymer, which contains other monomer units other than vinyl alcohol units and vinyl ester units, obtained by saponifying a copolymer, which is obtained by copolymerizing vinyl ester monomers, which are its raw material monomers, with other monomers. The vinyl ester monomer used as the raw material monomer for the vinyl alcohol-based polymer is not particularly limited, and examples include vinyl acetate. The other monomers are not particularly limited, and examples include ethylene, propylene, n-butene, isobutylene, and other α-olefins. The PVA-based resin preferably contains at least one selected from the group consisting of unmodified vinyl alcohol polymers and α-olefin-vinyl alcohol copolymers, and more preferably contains an unmodified vinyl alcohol polymer.

[0074] Furthermore, in one embodiment of the present invention, the PVA resin layer may contain a plasticizer such as a polyol (e.g., trehalose) in addition to the PVA resin. In this specification, "main component" means a component that is present in more than 50% by mass relative to the mass of the layer, and the amount may be, for example, 55% or more by mass, 70% or more by mass, or 90% or more by mass.

[0075] The type of paper used is not particularly limited and includes, for example, kraft paper, double-bleached kraft paper, fine paper, imitation paper, glassine paper, parchment paper, synthetic paper, white cardboard, Manila cardboard, milk carton base paper, cup base paper, ivory paper, and silver paper.

[0076] Examples of laminates of the present invention include laminates containing a biodegradable resin layer / adhesive layer in this order; laminates containing a PVA-based resin layer / adhesive layer in this order; and laminates containing a biodegradable resin layer / adhesive layer / PVA-based resin layer in this order. Among these, the laminate of the present invention is preferably a laminate containing a biodegradable resin layer / adhesive layer / PVA-based resin layer in this order (sometimes referred to as laminate A). These laminates may contain other layers besides the biodegradable resin layer and the PVA-based resin layer between or outside each layer, but it is preferable that there are no other layers between each layer, that is, that each layer is adjacent to the others. For example, in laminate A, it is preferable that the biodegradable resin layer, adhesive layer and PVA-based resin are arranged adjacent to each other (i.e., in contact) in this order. Laminate A has excellent adhesive strength between the biodegradable resin layer and the adhesive layer, and between the adhesive layer and the PVA-based resin layer, as well as heat resistance and biodegradability.

[0077] The thickness of the adhesive layer in the laminate of the present invention can be appropriately selected depending on the type of laminate and is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, and particularly preferably 50 μm or less. When the thickness of the adhesive layer is within the above range, it is easy to improve adhesive strength, heat resistance, biodegradability, and gas barrier properties. The above thickness of the adhesive layer refers to the thickness of one layer when the laminate contains two or more adhesive layers.

[0078] The thickness of the other layers in the laminate of the present invention can be appropriately selected depending on the type of laminate and is not particularly limited, but is preferably 10 to 3000 μm, more preferably 15 to 1000 μm, and even more preferably 20 to 500 μm. When the thickness of the other layers is within the above range, it is easy to improve adhesive strength, heat resistance, biodegradability, and gas barrier properties. The thickness of the other layers mentioned above refers to the thickness of one layer if the laminate contains two or more other layers.

[0079] The thickness of the laminate of the present invention is not particularly limited, but is preferably 20 μm or more, more preferably 50 μm or more, even more preferably 100 μm or more, even more preferably 200 μm or more, particularly preferably 300 μm or more, preferably 5000 μm or less, more preferably 3000 μm or less, and even more preferably 1000 μm or less. When the thickness of the laminate is within the above range, it is easier to improve the strength, heat resistance, biodegradability, and gas barrier properties of the laminate.

[0080] In one embodiment of the present invention, the thickness of the adhesive layer in the laminate A of the present invention is the same as the thickness of the adhesive layer described above. The thickness of the biodegradable resin layer in the laminate A is not particularly limited, but is preferably 50 μm or more, more preferably 100 μm or more, even more preferably 200 μm or more, preferably 1000 μm or less, and even more preferably 500 μm or less. Furthermore, the thickness of the PVA-based resin layer in the laminate A is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, preferably 1000 μm or less, more preferably 500 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, and especially preferably 50 μm or less. When the thickness of each layer is within the above range, it is easy to improve adhesive strength, heat resistance, biodegradability, and gas barrier properties. The thickness of each layer (biodegradable resin layer, adhesive layer, and PVA-based resin layer) in the laminate A described above refers to the thickness of one layer if there are two or more of the same layer in the laminate A. The thickness of each of the above layers and the thickness of the laminate can be measured using a thickness gauge, for example, by the method described in the examples.

[0081] The following are examples of specific layer configurations for the laminate A of the present invention. Biodegradable resin layer / adhesive layer / PVA resin layer; Biodegradable resin layer / adhesive layer / PVA resin layer / adhesive layer / biodegradable resin layer; Biodegradable resin layer / regrind layer / adhesive layer / PVA resin layer / adhesive layer / regrind layer / biodegradable resin layer; Biodegradable resin layer / adhesive layer / PVA resin layer / adhesive layer / paper.

[0082] The laminate of the present invention can be manufactured by laminating an adhesive layer with another layer, such as a resin layer, using conventional methods such as co-extrusion molding (co-extrusion lamination, co-extrusion sheet molding, co-extrusion inflation molding, co-extrusion blow molding, etc.), co-injection molding, extrusion lamination, or dry lamination. For example, the adhesive layer may be co-extruded or laminated with the other layer; or an adhesive resin composition may be formed into a film on the other layer. When laminating, the adhesive resin composition may be applied to the surface of the other layer or extruded onto the surface of the other layer.

[0083] A preferred embodiment of the present invention is a method for manufacturing laminate A, which is not particularly limited, but a preferred method is to co-extrude pellet-shaped adhesive resin composition, pellet-shaped biodegradable resin (or biodegradable resin composition) for forming a biodegradable resin layer, and pellet-shaped PVA-based resin (or PVA-based resin composition) for forming a PVA-based resin layer using a co-extruder. More specifically, each resin (or each resin composition) can be introduced into the hopper of each extruder, melt-kneaded, and co-extruded using a feed block die. The cylinder temperature of each extruder can be appropriately selected according to the melting temperature of the resin (or resin composition). Although not limited, for example, the cylinder temperature of the extruder for the adhesive layer may be, for example, 120 to 300°C, preferably 150 to 250°C, the cylinder temperature of the extruder for the biodegradable resin layer may be, for example, 150 to 300°C, preferably 180 to 250°C, and the cylinder temperature of the extruder for the PVA-based resin layer may be, for example, 150 to 300°C, preferably 190 to 260°C.

[0084] In one embodiment of the present invention, the laminate of the present invention also has excellent heat resistance, and for example, discoloration at high temperatures during manufacturing or molding can be suppressed or prevented. The laminate of the present invention also has excellent thermoformability and can be easily molded into a predetermined shape. In a preferred embodiment, no wrinkles or the like occur even when thermoformed. Therefore, the laminate of the present invention has excellent appearance. The molding method is preferably melt molding, and the melt molding method is not particularly limited, but examples include extrusion molding, injection molding, extrusion film formation from a T-die, inflation film formation, compression molding, transfer molding, reinforced plastic molding, hollow molding, press molding, blow molding, calendering, foam molding, vacuum molding, and pressure molding. If desired, other thermoplastic resins can also be laminated by methods such as co-extrusion molding and lamination molding. By these methods, molded articles of any shape, such as films, sheets, tubes, bottles, capsules, nonwoven fabrics, and fibers, can be obtained. In one embodiment of the present invention, when molding by vacuum molding, the laminate can be heated and then molded into a desired shape using a vacuum molding machine. The molding temperature is not limited and can be appropriately selected depending on the type of laminate, preferably 100°C or higher, more preferably 130°C or higher, even more preferably 150°C or higher, preferably 300°C or lower, and more preferably 200°C or lower. At such molding temperatures, it is easy to form a molded body with excellent thermoformability.

[0085] [Food packaging materials] The adhesive resin composition and laminate of the present invention are not particularly limited in their applications, but they are suitably used as packaging materials, especially food packaging materials. Therefore, the present invention encompasses food packaging materials, particularly coffee capsules, that include an adhesive layer comprising the adhesive resin composition of the present invention, or a laminate comprising the laminate of the present invention. Because the food packaging material of the present invention includes the adhesive layer or laminate of the present invention, it exhibits excellent adhesive strength, heat resistance, thermoformability, biodegradability, and gas barrier properties. Food packaging materials are not particularly limited, but examples include containers for packaging foods such as meat, fresh noodles, processed foods, tea, coffee powder, coffee beans, and pickles. In a preferred embodiment of the present invention, the food packaging material may be a rubber bag for organic waste, a container used at various events, a tea bag, a coffee capsule, etc., and is particularly suitably used as a coffee capsule. [Examples]

[0086] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited in any way by these examples. The measurement and evaluation methods for the following examples and comparative examples are shown below.

[0087] [Elongation at break] Sheets obtained by heat-press molding of biodegradable polyester resin were cut to a width of 15 mm and a length of 100 mm, and the elongation at break was measured in accordance with ISO 527-1.

[0088] [Melting point] For each example and comparative example, 10 mg of the resin composition pellets obtained was sealed in an aluminum pan (manufactured by TA Instrument Co., Ltd.), heated from -30°C to 220°C at a rate of 10°C / min, rapidly cooled to -30°C at a rate of 10°C / min, and then heated again from -30°C to 220°C at a rate of 10°C / min to perform DSC measurements. The melting point Tm (°C) was determined from the peak temperature of the temperature range from the start to the end of melting during the second heating step in the obtained DSC curve.

[0089] [MFR] Regarding the biodegradable polyester resin (A), the MFR was measured at 200°C under a load of 2.16 kg in accordance with JIS K7210:2014.

[0090] [Mw, Mn] The Mw and Mn of the biodegradable polyester resin (A) were measured using the relative molecular weight analysis method by GPC analysis described below. <Sample Preparation> Approximately 5 mg of a powder sample of the biodegradable polyester resin (A) was collected and precisely weighed. To the collected sample, 1 mL of hexafluoroisopropanol (HFIP) added with 20 mM sodium trifluoroacetate per 1 mg of the sample was added, and the mixture was heated at 40°C for 3 hours to dissolve the sample. Using this solution, GPC analysis was performed under the following conditions. The relative molecular weight distribution curve was calculated by converting the relative molecular weight obtained from the RI detector using the analysis software attached to the analyzer. The analysis was performed 3 times on the same sample, and the average value was taken as the analysis result.

[0091] <GPC Analysis Conditions> Measuring apparatus: HLC-8320GPC (manufactured by TOSOH Corporation) Analysis software: Empower (manufactured by Waters Corporation) Sample concentration: 0.1 mg / ml Mobile phase solvent: Hexafluoroisopropanol added with 20 mM sodium trifluoroacetate Injection volume: 10 μl Flow rate: 0.2 ml / min Measurement temperature: 40°C Sample dissolution conditions: 40°C × 3 hours Filtration: 0.45 μm PTFE filter Columns: 2 pieces of GMMHR-H(S) (manufactured by TOSOH Corporation) Detector: RI detector attached to the apparatus Calibration standard for apparatus: PMMA (manufactured by Agilent Technologies, Inc.)

[0092] [Thickness] The thicknesses of the sheets, laminates, and each layer within the laminates made of the adhesive resin compositions in the examples and comparative examples were measured using a digital micrometer.

[0093] [Glass transition temperature (Tg)] The Tg of polyol (B) was evaluated by DSC measurement under nitrogen conditions at a heating rate of 10°C / min.

[0094] [Adhesion strength of adhesive resin composition to PVA-based resin layer] The pellets of the adhesive resin compositions obtained in the examples and comparative examples were preheated at 180°C for 5 minutes using a compression mold, and then subjected to a load of 50 kgf / cm². 2 A film (also called an adhesive layer) made of an adhesive resin composition was obtained by compression molding for 30 seconds under these conditions. The film made of the adhesive resin composition (150 mm long x 150 mm wide x 0.3 mm thick), a polyimide film (Toray DuPont's "Kapton Film", 75 mm long x 150 mm wide x 0.05 mm thick), and a film made of polyvinyl alcohol resin (also called a PVA resin layer) (Kuraray's "Mobiflex C17", 150 mm long x 150 mm wide x 0.5 mm thick) were stacked in this order and placed in the center of a metal spacer with inner dimensions of 150 mm x 150 mm and a thickness of 0.8 mm. This stacked film and metal spacer were sandwiched between polytetrafluoroethylene sheets, and further sandwiched from the outside with metal plates, and molded using a compression molding machine at 180°C and a load of 50 kgf / cm². 2 By compression molding for 30 seconds, a multilayer sheet containing an adhesive layer and a PVA resin layer was obtained. The multilayer sheet was cut into 25 mm wide strips to serve as test pieces for measuring adhesive strength. The peel strength between the adhesive layer and the PVA resin layer was measured in accordance with JIS K 6854-2 using a peel tester (Shimadzu Corporation "AGS-X") under conditions of a peel angle of 180°, a tensile speed of 100 mm / min, and an ambient temperature of 23°C. This was defined as the adhesive strength of the adhesive resin composition to the PVA resin layer.

[0095] [Adhesion strength of adhesive resin composition to PLA (polylactic acid) resin layer] The pellets of the adhesive resin compositions obtained in the examples and comparative examples were subjected to a hot press (Shinto Metal Industries Co., Ltd. "Automatic Press SF-37") at 150°C and a load of 100 kgf / cm². 2 A film (also called an adhesive layer) made of an adhesive resin composition was obtained by compression molding for 30 seconds under these conditions. The film made of the adhesive resin composition (150 mm long x 150 mm wide x 0.5 mm thick), a polyimide film (UBE Corporation's "UPIREX", 75 mm long x 150 mm wide x 0.05 mm thick), and a film made of PLA resin (also called a PLA resin layer) (Nature Works' "Ingeo 2003D", 150 mm long x 150 mm wide x 0.3 mm thick) were stacked in this order and placed in the center of a metal spacer with inner dimensions of 150 mm x 150 mm and a thickness of 0.8 mm. This stacked film and metal spacer were sandwiched between polytetrafluoroethylene sheets, and further sandwiched from the outside with metal plates, and then pressed using a hot press machine at 180°C and a load of 50 kgf / cm². 2 By compression molding for 30 seconds, a multilayer sheet containing an adhesive layer and a PLA resin layer was obtained. The multilayer sheet was cut into 25 mm wide strips to serve as test pieces for measuring adhesive strength. The peel strength between the adhesive layer and the PLA resin layer was measured in accordance with JIS K 6854-2 using a peel tester (Shimadzu Corporation "AGS-X") under conditions of a peel angle of 180°, a tensile speed of 100 mm / min, and an ambient temperature of 23°C. This was defined as the adhesive strength of the adhesive resin composition to the PLA resin layer.

[0096] The adhesive strength was evaluated using the following indicators. The results are shown in Table 2. ◎: Peel strength of 25N / 25mm or higher ○: Peel strength of 5N / 25mm or more and less than 25N / 25mm ×: Peel strength less than 5N / 25mm

[0097] [Heat resistance evaluation] A circular capillary (diameter: 1 mm) was attached to a capillary rheometer (CAPIROGRAPH 1C, manufactured by TOYOSEIKI Corporation). The adhesive resin compositions obtained in the examples and comparative examples were left at a temperature of 200°C for 5 minutes, then extruded at a piston speed of 10 mm / min. The resulting strands were visually inspected for coloration, and their heat resistance was evaluated using the following indicators. The results are shown in Table 2. ◎: No coloring ○: Light brown coloring ×: Colored brown to black

[0098] [Example 1] <Adhesive resin composition> As biodegradable polyester (A), 100 parts by mass of polybutylene adipate terephthalate (BASF's "EcoflexFBlendC1200", melting point: 118℃, elongation at break: 1102%, MFR: 15.8g / 10min, Mw: 72000, Mn: 24500), as polyol (B), 10.0 parts by mass of maltitol (Itochu Sugar Co., Ltd.'s "Parisienne", Tg: 47℃), and, After dry blending 15.0 parts by mass of modified starch (C) ("Capsul®" manufactured by Ingredion, corn starch modified with octenyl succinic anhydride, weight-average molecular weight 32,000, average amylose content 1% by mass), the mixture was melt-kneaded under the following conditions using a twin-screw extruder KZW15-45MG (D=15mmφ, L / D=45, manufactured by Technovel Co., Ltd.). After extruding the molten mixture from a strand nozzle, the resulting strands were cooled and cut to obtain pellets of adhesive resin composition. [Table 1] Screw rotation speed: 250 rpm Operating method: Same direction, same rotation, fully meshed type

[0099] <Laminate> A laminate consisting of three types and five layers was fabricated using the following method, in which a biodegradable resin layer / adhesive layer / polyvinyl alcohol-based resin layer / adhesive layer / biodegradable resin layer was laminated in this order. The pellets of the adhesive resin composition obtained above, the pellets of the polyvinyl alcohol-based resin composition (a composition obtained by kneading 100 parts by mass of ethylene-vinyl alcohol copolymer (A1) and 67 parts by mass of trehalose in a twin-screw extruder), and the pellets of polylactic acid (Natureworks, Ingeo®, biopolymer 2003D) were each fed into the hopper of a single-screw extruder (GMENGINEERING, VGM25-28EX), and co-extruded at a flow rate of 5 kg / h using a feed block die to obtain a laminate of 3 types and 5 layers with a width of 20 cm. At this time, the set cylinder temperatures were as follows. (Cylinder temperature) Adhesive layer: 180°C, Polyvinyl alcohol-based resin layer: 210°C, Biodegradable resin layer: 220°C

[0100] The resulting laminate had the following structure from the outside in: polylactic acid layer / adhesive layer / polyvinyl alcohol-based resin layer / adhesive layer / polylactic acid layer = 250 μm / 20 μm / 30 μm / 20 μm / 250 μm (thickness).

[0101] [Examples 2-11 and Comparative Examples 1-5] Except for changing the types and amounts of biodegradable polyester resin (A), polyol (B), and modified starch (C) used in the preparation of the adhesive resin composition as shown in Table 2, an adhesive resin composition and laminate were obtained in the same manner as in Example 1. In Table 2, the same PBAT and maltitol as in Example 1 were used, sorbitol was "D(-)-sorbitol" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Tg: -4℃, trehalose was "Treha" manufactured by Hayashibara Corporation, Tg: 120℃, and glycerin was "glycerin" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Tg: -75℃. In addition, the PBAT used in the examples and comparative examples met the biodegradability criteria specified in EN13432 and ASTM6400.

[0102] Following the method described above, the peel strength of each adhesive resin composition obtained in the examples and comparative examples was measured against the PLA resin layer and the PVA-based resin layer, respectively, and the adhesive strength was evaluated. In addition, the heat resistance of each adhesive resin composition was evaluated. The results are shown in Table 2. In Table 2, "cohesive failure" refers to the failure of the film (adhesive layer) made of the adhesive resin composition before peeling in the peel test. For films (adhesive layers) that underwent cohesive failure, the adhesive strength was evaluated based on the strength at the time of cohesive failure. The numbers in parentheses indicate the strength at the time of cohesive failure, and *1 indicates that the material was too brittle to measure the strength at the time of cohesive failure. [Table 2]

[0103] As shown in Table 2, the adhesive resin compositions of Examples 1 to 11 were confirmed to have high adhesive strength to both the PVA-based resin layer and the PLA resin layer, as well as high heat resistance. In contrast, the adhesive resin compositions of Comparative Examples 1 to 5 were confirmed to have inferior evaluations in at least one of these areas. Therefore, the adhesive resin composition of the present invention has excellent heat resistance and excellent adhesive strength to both the PVA-based resin layer and the biodegradable resin layer.

Claims

1. Based on 100 parts by mass of biodegradable polyester resin (A), the mixture contains 3 to 24 parts by mass of polyol (B) and 0 to 40 parts by mass of starch or modified starch (C), with the total amount of polyol (B) and starch or modified starch (C) being 44 parts by mass or less, the biodegradable polyester (A) having a break elongation of 50% or more as measured in accordance with ISO 527-1, and the glass transition temperature of polyol (B) being -10°C or higher. The polyol (B) is at least one selected from the group consisting of maltitol, sorbitol, and trehalose, wherein, if the polyol (B) is trehalose, the trehalose content is 20.5 parts by mass or more based on 100 parts by mass of biodegradable polyester resin (A), in an adhesive resin composition.

2. The adhesive resin composition according to claim 1, wherein the melting point of the biodegradable polyester resin (A) is 70°C or higher.

3. The adhesive resin composition according to claim 1, wherein the biodegradable polyester resin (A) includes an aromatic-aliphatic copolymer polyester resin.

4. The adhesive resin composition according to claim 3, wherein the aromatic-aliphatic copolymer polyester resin is polybutylene adipate terephthalate.

5. The adhesive resin composition according to claim 1, which does not contain starch or modified starch (C).

6. A laminate comprising an adhesive layer comprising the adhesive resin composition according to any one of claims 1 to 5.

7. The laminate according to claim 6, comprising a biodegradable resin layer, the adhesive layer, and a polyvinyl alcohol-based resin layer in this order.

8. A food packaging material comprising an adhesive layer comprising the adhesive resin composition according to any one of claims 1 to 5.

9. A coffee capsule comprising an adhesive layer comprising the adhesive resin composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Resin composition and its molded product

    JP2003335934A

  • Laminated film

    JP2009208398A

  • Adhesive resin composition, laminate and molding

    JP2019157005A

  • Biodegradable laminate

    JP2019181943A

  • Resin composition and method for producing the same

    JP2021172824A